2017
DOI: 10.1186/s40101-017-0127-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory and metabolic responses to body mass-based squat exercise in young men

Abstract: BackgroundThe purpose of this study was to quantify cardiorespiratory and metabolic responses to body mass-based squat exercise, with specific emphasis on the relationships with the exercise duration.MethodsFifteen healthy young men performed body mass-based squat exercise as well as an incremental loaded bicycle test, which determine maximal oxygen uptake and maximal heart rate, with an interval of 2 days between the tests. During both tasks, oxygen uptake, blood lactate concentration (BLa), and heart rate (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Haramura et al. ( 2017 ) showed that body mass‐based squats exercise is of moderate intensity and involves aerobic metabolism after 5 min from exercise onset in healthy young men (Haramura et al., 2017 ). From these previous studies, body mass‐based RT was expected to have aerobic training aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haramura et al. ( 2017 ) showed that body mass‐based squats exercise is of moderate intensity and involves aerobic metabolism after 5 min from exercise onset in healthy young men (Haramura et al., 2017 ). From these previous studies, body mass‐based RT was expected to have aerobic training aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Body mass‐based resistance exercise (e.g., squats), which can be performed by everyone anywhere, are feasible and effective for improving knee extensor muscular strength in older adults (Yoshiko & Watanabe, 2021 ) and body fat percentage and knee extensor muscular strength in adolescents (Takai et al., 2013 ). Interestingly, in young men, body mass‐based squat exercises involve aerobic metabolism after 5 min from exercise onset (Haramura et al., 2017 ). This indicates that body mass‐based resistance exercise would be predominately supported by aerobic metabolism when continuously performed.…”
Section: Introductionmentioning
confidence: 99%
“…After 200 training cycles, the loss of the network decreased to 0.9, and the network did not converge. In previous squat tests, no uniform squat range was achieved and no uniform control method for the squatting range was formed [32][33][34]. In this case, even if the standard for evaluating individual cardiopulmonary function by IST was established, the results would be meaningless owing to different squat ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific RepoRtS |(2020) 10:1815 | https://doi.org/10.1038/s41598-020-58791-0www.nature.com/scientificreports www.nature.com/scientificreports/ on an individual's maximal aerobic power54 . In future studies, VO 2max will be tested and used as a factor to analyze its influence on metabolic variables.…”
mentioning
confidence: 99%